Removal of cu2+ using utricularia aurea as a biosorbent in synthetic industrial wastewater - Akbar, Nor Azliza; Abu Bakar, Amalina Amirah; Mat Daud, Nurhidayati; Badrealam, Sabariah; Ahmad Tarmizi, Nurul Athirah (Universiti Teknologi MARA Cawangan Pulau Pinang, 2017)
Biosorption of copper ions (Cu2+) using Utricularia Aurea has been investigated as a function of pH, contact time and particle size of the biosorbent. A series of batch equilibrium adsorption study was conducted to determine the effect of varied pH from pH 2, 4, 7, and 9, contact time at 30, 60, 90 and 120 minutes, biosorbent particle size ranging from 150 µm, 300 µm, 450 µm and 600 µm at an agitation speed of 125 rpm using Utricularia aurea (U. Aurea). Based on the optimization study, it was found that the optimum removal of Cu2+ (>90%) occurred at pH4, contact time of 40 minutes and particle size of 450µm. Atomic Absorption Spectrometer was used to analyse the concentration of Cu2+ in the sample. A kinetic study on Cu2+ adsorption onto U.Aurea was analysed using pseudo-first order and pseudo second order kinetic models. Based on the kinetic study analysis, the adsorption of Cu2+ followed pseudo- second order kinetic which r2 was greater than 0.99 rather than pseudo- first order kinetic models. Thus, Utricularia Aurea can be an alternative as a new adsorbent media in treating heavy metals contaminated for industrial wastewater.